Anxiety, Despair And The Knight Of Faith: The Ontological, The Ontic And The Transcendent in Søren Kierkegaard (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Two cases in the existential-phenomenological literature, Ellen West and Rita, are re-examined in the light of Kierkegaard's powerful critique of Anxiety and Despair in his so-called 'psychological works'. An attempt is made to show how Kierkegaard's ideas can be humanized and secularized for the work of therapy.
Keywords: Kierkegaard; existentialism; anxiety; despair; bereavement; psychotherapy; Binswanger; van Deurzen